Dietary soy isoflavones during pregnancy suppressed the immune function in male offspring albino rats - Gaffer, Ghada Gamal (Toxicol Rep, 2018)
Phytoestrogens have an impact on both animals and humans due to use of legumes in animal diets as well as the increase of vegetarian diets in some human populations. Phytoestrogens thought to have varieties of adverse effects, among which immune system was involved. The present study aimed to investigate the effect of prenatal exposure to dietary soy isoflavones on some immunological parameters in male albino rat offspring. The pregnant rats were divided to three groups (12/group). Control group (free soy isoflavones), low soy isoflavones group (6.5%) and high soy isoflavones group (26%). The male offspring cell-mediated immune response was determined using phytohemagglutinin (PHA) injection and the intumesce index which was calculated on postnatal day 50 (PND 50). At PND 50, blood samples were collected for interleukin 12 (IL-12), interferon γ (IFN-γ) and tumor necrosis factor α (TNF-α) determination. Spleen, thymus, and PHA injected footpads were fixed for histopathology. Intumesce index, IL-12, IFN-γ, spleen and thymus relative weights were significantly (P < 0.05) decreased in offspring born to dams fed low and high dietary soy isoflavones. In contrary, TNF-α was significantly (P < 0.05) increased in offspring born to dams fed high dietary soy isoflavones. Spleen of rats born to dams fed high dose of dietary soy isoflavones showed coagulative necrosis in white pulp. In conclusion, male offspring born to dams fed different levels of soy isoflavones showed marked immunosuppression after PHA stimulation. This effect was mediated through the reduced IFN-γ that interacts with the IL-12 production pathway.